Factores de gestión del conocimiento en entidad pública del sector de tránsito y transporte; Knowledge factors in public entity of the transit and transport sector - Erick Orozco Acosta; Luis Ortiz-Ospino; Doris Padilla-Suárez; Analida Pizarro Gutiérrez (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2021)
– From a systemic perspective, knowledge management affects the decision-making process in organizations that, in a globalized environment, must propose strategies that make it possible to increase competitiveness and productivity. The objective is to determine the knowledge management factors (GC) in a public entity of the transport sector in Colombia that optimize the provision of its services, offering tools that facilitate the capture, creation, retention, dissemination and use of knowledge, taking as a reference, the Relational analysis of four factors such as information management, strategic planning, communication and incentives and technological management. The research is quantitative in approach, with a correlational scope and a non-experimental cross-sectional design. Multivariate statistical techniques were applied in the data analysis. A correlational analysis was performed through the calculation of the Sperman correlation coefficient, to establish how the relationships between the dimensions of the factors studied and between each factor are. The factors are then validated through an analysis of structural equations with maximum likelihood estimates. Among the findings found it is highlighted that there is no association between information management and technological management, which limits the management of organizational knowledge but in turn constitutes an opportunity for improvement for the effective future execution of the processes.
Keywords: C12; C35; H87; L98; 330; knowledge management; models; technology; decision making